How New and Expecting Fathers Engage With an App-Based Online Forum: Qualitative Analysis. - White, B.; Giglia, R.; Scott, Jane; Burns, S. (2018)
BACKGROUND: Breastfeeding is important for infants, and fathers are influential in supporting their partner in their decision to breastfeed and how long they breastfeed for. Fathers can feel excluded from traditional antenatal education and support opportunities but highly value social support from peers. Online health forums can be a useful source of social support, yet little is known about how fathers would use a conversation forum embedded in a breastfeeding-focused app. Milk Man is a mobile app that aimed to increase paternal support for breastfeeding using a range of strategies, including a conversation forum. OBJECTIVE: The aim of this study was to examine how fathers used a breastfeeding-focused conversation forum contained within a mobile app throughout the perinatal period. METHODS: A qualitative analysis of comments posted by users in the online forum contained within the Milk Man app was conducted. The app contained a library of information for fathers, as well as a conversation forum. Thematic analysis was used to organize and understand the data. The NVivo 11 software package was used to code comments into common nodes, which were then organized into key themes. RESULTS: In all, 208 contributors (35.5% [208/586] of those who had access to the app) posted at least once within the forum. In total, 1497 comments were included for analysis. These comments were coded to 3799 individual nodes and then summarized to 54 tree nodes from which four themes emerged to describe how fathers used the app. Themes included seek and offer support, social connection, informational support provision, and sharing experiences. Posting in the forum was concentrated in the antenatal period and up to approximately 6 weeks postpartum. CONCLUSIONS: These data show that fathers are prepared to use a breastfeeding-focused online forum in a variety of ways to facilitate social support. Fathers can be difficult to reach in the perinatal period, yet engaging them and increasing social support is important. This research demonstrates the acceptability of an innovative way of engaging new and expecting fathers.